Service Quality Dimensions and Customer Satisfaction in Malaysian Mobile Telecommunication Market: An Empirical Investigation of the Mobile Phone Market in Malaysia. (Global Business Management Review (GBMR), 2022)
This paper aim to examine the relationship between service quality dimensions and customer satisfaction in Malaysian mobile telecommunication market. The population of this study comprised of Malaysian mobile phone subscribers, the sample size was 112 and it was selected with simple random sampling technique. The data collection method was based on personally administered questionnaires to the respondents. Out of 112 questionnaires, 103 questionnaires were collected, and 9 questionnaires were not returned by the respondents. Moreover, the results of this study show service quality dimensions have positive relation effects on customer satisfaction in Malaysian mobile telecommunication market.